Susceptible Factors, Awareness And Health Care Management Of Covid-19 Patients Discharged From A Tertiary Hospital In The Pune District (Journal of Pharmaceutical Negative Results, 2023)
INTRODUCTION: Coronavirus disease (COVID-19), an infectious disease caused by a new coronavirus called SARS-CoV-02, causes mild to moderate respiratory illness, and patients with benign disease conditions recover without requiring special treatment.The best way to prevent and slow down transmission is to be well-informed about the COVID-19 virus, the disease, its causes, and how it spreads; hence a qualitative research tool using focus group discussion was carried out with the following objective.To determine various symptoms, awareness, course of the disease, and health care impact on COVID-19 cases seeking health care.METHODOLOGY: A cross-sectional qualitative study was conducted at a tertiaryhospital attached to a medical college in April 2020. Information about the discharge of patients with a number equal to or more than 12 patient groups and their ward numbers was obtained from the office of the hospital’s CEO. The collective proportion of content analysis of all the groups interacted, Word cloud, text mining, and ATLAS-TI software were used for analysis.RESULTS: The investigator interacted with the groups until saturation in reply was achieved. The average age group was 41 years. 91% of patients ranged from middle-aged adults. There were 62% male and 38 % female patients. The patients could recollect and guess the likely source of infection. A specific inquiry was made to remind them to obtain the answers. Those aware of the confirmed case, either in the family, relatives, workplace, neighbours, or mass testing of patients in their chawl, could guess the reason for their positivity.CONCLUSION: Health experts should remove the fear among the patient during such pandemic situations after the patients enter isolation. The patients experienced stigma from the society they lived in.